2015
DOI: 10.5194/hess-19-1849-2015
|View full text |Cite
|
Sign up to set email alerts
|

Erosion processes in black marl soils at the millimetre scale: preliminary insights from an analogous model

Abstract: Abstract.To investigate the millimetre-scale surface processes caused by natural rainfall, an undisturbed sample of badlands soil (1 m long, 0.5 m wide and 0.15 m thick) was carefully extracted. The sample is composed of black marl soil from a badlands area of the Draix Observatory (SE France). After extraction, the undisturbed sample was placed at the same slope angle (45 • ) as its original orientation and was then monitored for several processes via a terrestrial laser scanner (TLS) with millimetre-scale ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The value of eroded volumes based on the sediment trap is increased by 20 % to include the suspended sediments; otherwise the true erosion rates are un-derestimated. In addition, although the swelling or inflation of the regolith surface (Bechet et al, 2015) can have an influence on the georeferencing, it was not possible to quantify it at the level of the Roubine catchment. Nevertheless, it has been shown that the unweathered black marl density is 2650 kg m −3 , while the regolith density can be as small as 1300 kg m −3 , but it varies greatly in space and time according to the presence of local discontinuities (Maquaire et al, 2003;Travelletti et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of eroded volumes based on the sediment trap is increased by 20 % to include the suspended sediments; otherwise the true erosion rates are un-derestimated. In addition, although the swelling or inflation of the regolith surface (Bechet et al, 2015) can have an influence on the georeferencing, it was not possible to quantify it at the level of the Roubine catchment. Nevertheless, it has been shown that the unweathered black marl density is 2650 kg m −3 , while the regolith density can be as small as 1300 kg m −3 , but it varies greatly in space and time according to the presence of local discontinuities (Maquaire et al, 2003;Travelletti et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…First, the vegetated areas are deleted from the raw point clouds in order to keep only the bare soil surface for the analysis. The scans of each campaign are then aligned using the iterative closest point (ICP) procedure (Chen and Medioni, 1992;Besl and McKay, 1992) to obtain a point cloud of the entire catchment. The TLS campaigns are aligned to a reference campaign (e.g.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Portillo-Quintero et al (2014) used an ATLS to map daily changes in Plant Area Index (PAI) for a period of 22 days during leaf drop in a Boreal-Mixed forest. To study dynamic changes in soil microtopography under changing weather conditions, Bechet et al (2015) tracked rainfall simulation induced microtopographic changes with hypertemporal lidar. For monitoring snowpack dynamics and snow avalanches, Adams et al (2013) acquired lidar data with an ATLS of a mountainside in the Austrian Alps twice per day for a period of five months (February 5 th 2013 to June 6 th 2013).…”
Section: Hypertemporal Lidarmentioning
confidence: 99%
“…The results showed that the geomorphology of badlands has been extensively studied for the last 30 years, using numerous methods to understand geomorphological dynamics (erosion and deposition processes) and quantify erosion rates. The authors emphasized that from 2007 there has been a sharp increase in topographic data measurements for geomorphic research (Nadal-Romero et al, 2015), and new developments and non-invasive tools have focused on constructing Digital Elevation Models (DEMs) or Digital Terrain Models (DTMs): Structure from Motion photogrammetry (SfM) (Gómez-Gutiérrez et al, 2014Castillo et al, 2015;Smith and Vericat, 2015), Terrestrial Laser Scanner (TLS) (Vericat et al, 2014;Bechet et al, 2015), or aerial SfM using Unnamed Aerial Vehicles (UAVs) (D´Oleire-Oltmanns et al, 2012;Neugirg et al, 2016b). These new technologies have provided a set of tools that are dramatically increasing spatial resolution and allowing new kinds of data analysis.…”
Section: Introductionmentioning
confidence: 99%